1998
DOI: 10.3109/03639049809082354
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes as Oral Delivery Systems for Human Insulin

Abstract: The use of different forms of human red blood cells as oral carrier systems for human insulin in vivo was the subject of this investigation. Male Wistar rats were made diabetic by a single intraperitoneal injection of streptozocin (100 mg/kg). Three days after the injection, rats were found diabetic as evidenced by elevated fasted blood glucose concentration (200 mg/dl or higher). Rats received orally one of the following (100 U, 2 ml): an insulin solution, a ghosts-insulin suspension, a vesicles-insulin suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Examples of pharmacological and imaging agents encapsulated into carrier RBC include diverse enzymes29,30, fluorescent labels30, erythropoietin for sustained stimulation of hemopoietic potential31, hemoglobin cofactor inositol hexaphosphate for enhancing RBC oxygen carrying capacity32,33, anti-thrombotic drugs heparin34 and thrombolytics35, amikacin for anti-parasitic therapy36,37, insulin38, fluoro-AMP25 and methotrexate for cancer chemotherapy35, isotopes for imaging of blood pool using gamma-scintigraphy and MRI39–42, antisense oligonucleotides for gene knock-outs43 and anti-viral interventions44, plasmid DNA for gene therapy45, and, more recently, magnetic nanoparticles46.…”
Section: Vascular Delivery Of Drugs Encapsulated Into Carrier Rbcmentioning
confidence: 99%
“…Examples of pharmacological and imaging agents encapsulated into carrier RBC include diverse enzymes29,30, fluorescent labels30, erythropoietin for sustained stimulation of hemopoietic potential31, hemoglobin cofactor inositol hexaphosphate for enhancing RBC oxygen carrying capacity32,33, anti-thrombotic drugs heparin34 and thrombolytics35, amikacin for anti-parasitic therapy36,37, insulin38, fluoro-AMP25 and methotrexate for cancer chemotherapy35, isotopes for imaging of blood pool using gamma-scintigraphy and MRI39–42, antisense oligonucleotides for gene knock-outs43 and anti-viral interventions44, plasmid DNA for gene therapy45, and, more recently, magnetic nanoparticles46.…”
Section: Vascular Delivery Of Drugs Encapsulated Into Carrier Rbcmentioning
confidence: 99%
“…It is quicker and cheaper method in comparison with other two. Al-Achi et al [95,96] have successfully reported erythrocyte membrane vesicular delivery of insulin and doxorubicin. Electrical breakdown method is used to convert ghosts into small vesicles under the influence of electrical potential.…”
Section: Nanoerythrosomes [Nes]mentioning
confidence: 99%
“…[105] In another approach of Al-Achi insulin solution either free or along with carrier that is, erythrocyte-ghosts (EG) or liposomes-vesicles, was administered buccally. Result showed decrease in blood glucose concentration.…”
Section: Erythrocytesmentioning
confidence: 99%